دراسة مقارنة بين الذكور والاناث في القدرات الحس حركية لتلامذة المرحلة الابتدائية بعمر(6-9) سنوات - وطفى ألفت; حيدر ميادة (Latakia University Journal -Medical Sciences Series, 2018)
هدفت الدراسة الحالية إلى التعرف على الفروق بين الذكور والاناث في قدرات الادراك الحس- حركي للتلاميذ بعمر (6-9) سنوات من خلال التركيز على خصائص هذه المرحلة العمرية ومعرفة فيما إذا كان هناك اختلاف في هذه القدرات تبعا لمتغير الجنس ولهذا الغرض تم اجراء المقارنة بين الذكور والاناث في مظاهر هذه القدرات للمرحلة العمرية التي تعد خصائصها متشابهة للجنسين. وتكونت عينة البحث من 60 تلميذاً وتلميذة من تلاميذ مدرسة ايهم ملاح في اللاذقية وتم استخدام المنهج الوصفي بأسلوب الدراسات المقارنة. توصلت الدراسة إلى انه لا يوجد فروق ذات دلالة احصائية بين الاناث والذكور في قدرات الادراك الحس –حركي بعمر (6-9) سنوات ,كما توصلت الدراسة الى ان نمو قدرات الادراك الحس – حركية لدى الأطفال بعمر (6-9) سنوات تنمو بصورة متساوية لكلا الجنسين اذا ما تعرضوا لنفس المتغيرات التعليمية والبيئية. فهم يعيشون في مجتمع واحد ويتعلمون في ذات المدرسة ويخضعون لنظام تعليمي موحد . The current piece of research aims to identify the discrepancies among males and females in relation to the kinetic-perceptual recognition capabilities for students aging (6-9) years. This is done through focusing on the characteristics of this age group, and realizing whether or not there is a difference accompanying such capabilities due to the gender-variable .For this purpose, a comparison has been conducted between males and females regarding he features of the capabilities such as age-group capabilities, the characteristics of which are alike for both sexes. The study sample includes 60 fe/male students at Ayham Mallah School in Lattakia. The descriptive comparative approach has been used. The study concludes that there are no statistical discrepancies between males and females in relation to kinetic-perceptual capabilities for students aging (6-9) years. It also concludes that the kinetic-perceptual recognition capabilities for such age-group students equally develop with both sexes whenever they are exposed to similar ecological and educational variables, and they live in one community and learn at the same school and they are subject to a uniform education system.